Health assets in transgender adolescents: The role of socio-political engagement and competence. (20th October 2021) - Moreno-Maldonado, C; Ciria-Barreiro, E; Rivera, F; Luna, S; Moreno, C
Abstract: Background: Research has shown lower mental health in transgender youth compared to cisgender peers. However, little is known about assets in their development. Self-determination theory posits that certain behaviours increase wellbeing, such as engaging in activities that meet the psychological need for competence and relatedness. This study analyses the mediator roles of political interest, sense of unity, and social self-efficacy in the association between gender identity and health. Methods: Two samples of Spanish adolescents (15-18 years-old) were analysed. The first sample included 170 transgender and 575 cisgender (selected through a matching process) students who participated in the 2018 Health Behaviour in School-Aged Children study. The second sample included 67 transgender and 2, 100 cisgender participants who collaborated in the UNICEF OPINA Barometer. Political interest, social self-efficacy, and sense of unity scales were used to measure community engagement and were considered as sources of resilience. Health-related quality of life (HRQL) was measured using the Kidscreen-10 scale. Data analysis was conducted using linear regressions and parallel mediation effects. Results: Gender identity predicted well-being, showing lower HRQL in transgender adolescents than cisgender peers. Furthermore, sense of unity and social self-efficacy - but not political interest - significantly predicted wellbeing (higher levels have a positive impact on HRQL) in both groups, and indirectly mediated between gender identity and HRQL. Conclusions: Sense of unity and social self-efficacy act as sources of resilience, increasing adolescent wellbeing. Thus, social inclusion and active citizenship can help adolescents to better cope with pressure and promote health. Moreover, the positive contributions of sense of unity and social self-efficacy was similar for cisgender and gender minority adolescents, suggesting similar underlying mechanisms.